Dukungan Sosial Orang Tua Anak dengan Down Syndrome dalam Grup WhatsApp - Azzumar Adhitia Santika; Firstty Soraya Anugraheny; Yasmin Alvina (Universitas Medan Area, 2020)
Discrimination towards children with down syndrome is still happening. Courtesy stigma concept makes parents with down syndrome children feel discrimination. Parents are the sole social support of the child. POTADS purpose as a platform for other Indonesiansâ€™ parents and children to show their support with each other who faced the same problem. They can support it through WhatsApp group and open for anyone who faced discrimination. Phenomenology method used to find how the consciousness of four informants called by Mrs. Leli, Mrs. Ni Luh, Mrs. Ernie, and Mrs. Nunung in using POTADS WhatsApp group. The conscious experiences will create an interpretation of it. In-depth interviews were conducted to obtain research data. The result shows that this group is beneficial because, in addition to being able to get useful information support for childcare, they also get the emotional support that is useful as a shield against courtesy stigma. The support they get from the WhatsApp group is further enhanced when there is a face-to-face meeting.Â